Interpersonal Privacy and the Fourth Amendment - Alschuler, Albert W. (Northern Illinois University law review, 1983)
A preliminary examination of the extent to which the fourth amendment protects the privacy of interpersonal relationships and of information or property that one person has shared with another, focusing particularly on the need for subjecting the informant system to additional judicial control